Identification of Sprawl Development Typologies around Toll Road Gates in Java, Indonesia - Rendy Bayu Aditya; Zumarotul Husna (TATALOKA, 2022)
In the last 2 decades, hundreds of kilometers of toll roads have been built on Java, stretching from the east to the west of the island. Many researchers have examined the impact of the physical development of toll roads. From these previous studies, no one had ever identified the types of sprawl development resulting from toll gates. The purpose of this research is to identify the types of sprawl developments caused by the existence of toll gates. This research uses 2 methods: spatial development analysis using Google Earth Pro and literature reviews from publications on the topic of the impact of toll gates. We selected 12 toll gates based on the following criteria: toll gates must represent the western, central, and eastern regions of Java Island & toll gates must represent the time periods of toll development, which were more than 2 decades old, under 2 decades old, and less than 1 decade. The findings show there are variety of sprawl development as a result of the existence of toll gates or exits. The three types of sprawl developments include (1) linear/corridor and leapfrog; (2)concentric/radial and leapfrog and (3) a combination of linear and radial coupled with a leapfrog.